164 Cardiosphere-Derived Cell-Seeded Porous Collagen Scaffolds for Cardiac Repair. (3rd June 2016) - Bruyneel, Arne; Nazir, Rabia; Chen, Qi; Lopez, Colleen; Czernuszka, Jan; Carr, Carolyn
Abstract : Irrespective of cell type, stem cell therapy to prevent heart failure following myocardial infarction is beset by low donor cell retention. Cell loss may be prevented by immobilisation within a supporting scaffold for application across the infarct, but cells must remain viable while vasculature develops into the scaffold. Previously we have shown that cardiosphere derived cells (CDCs) can be cultured on porous collagen scaffolds (Chen et al, J. Tissue. Sci. Eng. 2012). Here we investigate whether CDC-seeded collagen scaffolds, cultured under hypoxia to induce release of angiogenic growth factors, can improve cardiac function when applied to the infarcted rat heart. Methods: Porous collagen scaffolds were prepared by freeze-drying a suspension of type 1 collagen (1% wt/v.in 0.05M acetic acid (pH 3.2)) on a smooth film prepared by air-drying the collagen suspension. CDCs were isolated and expanded from male Sprague Dawley rats according to published protocols (Carr et al, PLoS One 2011). 10^5 CDCs were seeded onto the porous collagen scaffolds and cultured in hypoxia (5% oxygen) for 7 days. Myocardial infarction was induced in female Sprague Dawley rats with reperfusion after 40 minutes, at which point the scaffold was sutured to the infarct region of the heart. Hearts (4 groups: sham, infarct, infarct+scaffold, infarct+scaffold+cells, n = 5-–6 per group) were scanned in vivo using MRI at 1 week, 6 weeks and 12 weeks post MI. Results: CDC-loaded scaffolds cultured under hypoxia released significantly more VEGF than those cultured under normoxia. Bi-layer scaffolds could be sutured to the myocardium with the collagen film on the out-facing surface to reduce adhesion to the chest wall. Scaffolds without cells were attached to the infarcted heart for 2 or 6 weeks. At 2 weeks the scaffold had not fully integrated with the myocardium but by 6 weeks scaffolds were integrated and had begun to be degraded. Histological analysis showed substantial macrophage infiltration at 2 weeks and formation of blood vessels within the scaffold after 2 and 6 weeks. MRI of all four treatment groups showed that ejection fraction was significantly lower in all infarcted hearts at all time points but there was no significant difference in cardiac function between untreated infarcted hearts and those treated with scaffolds, with or without cells. By 12 weeks, in the majority of cases, no remnants of the scaffold could be detected by visual inspection. Conclusion: CDC-loaded collagen scaffolds could be attached to the infarcted heart but did not improve cardiac function. Scaffolds took time to merge with the myocardium although infiltration of macrophages and blood vessels occurred before scaffolds were fully integrated.